Preferential use of A- and U-rich codons for Mycoplasma capricolum ribosomal proteins S8 and L6. - Muto, A (1984)
The nucleotide sequence of the 1.3 kilobase-pair DNA segment, which contains the genes for ribosomal proteins S8 and L6, and a part of L18 of Mycoplasma capricolum, has been determined and compared with the corresponding sequence in Escherichia coli (Cerretti et al., Nucl. Acids Res. 11, 2599, 1983). Identities of the predicted amino acid sequences of S8 and L6 between the two organisms are 54% and 42%, respectively. The A + T content of the M. capricolum genes is 71%, which is much higher than that of E. coli (49%). Comparisons of codon usage between the two organisms have revealed that M. capricolum preferentially uses A- and U-rich codons. More than 90% of the codon third positions and 57% of the first positions in M. capricolum is either A or U, whereas E. coli uses A or U for the third and the first positions at a frequency of 51% and 36%, respectively. The biased choice of the A- and U-rich codons in this organism has been also observed in the codon replacements for conservative amino acid substitutions between M. capricolum and E. coli. These facts suggest that the codon usage of M. capricolum is strongly influenced by the high A + T content of the genome.